Urbanization, Biodiversity and Ecosystem Services: Challenges and Opportunities. A Global Assessment - Thomas Elmqvist; Michail Fragkias; Julie Goodness; Burak Güneralp; Peter J. Marcotullio; Robert Ian McDonald; Susan Parnell; Maria Schewenius; Marte Sendstad; Karen C. Seto; Cathy Wilkinson (Springer, 2013)
To understand how the world's ecosystems are changing we need to understand cities, and to create better cities we need to understand the ecosystems they depend on. The failure of most markets, government policies and even urban studies to take these relations into account has put cities, and increasingly the whole world, in a difficult position. Studies like Urbanization, Biodiversity and Ecosystem Services can help us to extricate ourselves, provided we act on the knowledge they provide (Gordon McGranahan, International Institute for Environment and Development). The challenges of urbanization are profound, but so too are the opportunities. Cities can reconcile human society and biodiversity by creating environments that are ecologically sustainable, economically productive, socially just, politically participatory and culturally vibrant. I commend this study to all who have a stake in creating ecologically sustainable urbanization for the benefit of humanity and the planet (Ban Ki-moon Secretary-General, United Nations).
Keywords: 300; Biodiversity; Challenges; Ecosystem services; Opportunities; Urbanization